Process Management in Design and Construction. - Cooper, Rachel (John Wiley & Sons, 2008)
Process management enables efficiency improvements by identifying and integrating generic sub-processes. This book provides a comprehensive introduction to process management in design and construction in order to meet the business needs of the construction industry as they change in a highly competitive global environment. The book identifies the current state of the industry in the process management field, illustrates current trends and developments and demonstrates these through case study evidence. It also provides practical guidance by identifying possible pitfalls and illustrate best pr.